KLASTER IQTISODIYOTINING NAZARIY ASOSLARI - Qosimov Saidahrol Magrufovich, Toxirov Akbarxon Toirxon o’g’li, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
A section is devoted to the cluster economy. Reveals its positive effects. Discusses the key factors contributing to the potential of cluster economy. Shows the impact of the cluster economy on the competitiveness factor. Attention is paid to the origin and classification of clusters on various grounds.